2020
DOI: 10.1080/03088839.2020.1730010
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of maritime accidents along the main route of the Maritime Silk Road: a Bayesian network approach

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Future investigations should be interdisciplinary, addressing not just the ecological challenges of coastal development in these regions, but also the social, cultural, economic, and political challenges in these unique contexts. Finally, studies are emerging that quantify the risks from new shipping routes and increasing traffic along the Maritime Silk Road on economic growth 42 , maritime accidents 23 , and carbon emissions 43 , yet the risks to vulnerable habitats and species have yet to be quantified and analyzed in depth. In addition to the features considered in this study, more research is needed investigating how the Maritime Silk Road may impact species’ behaviors, migration patterns, and the spread of invasive species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future investigations should be interdisciplinary, addressing not just the ecological challenges of coastal development in these regions, but also the social, cultural, economic, and political challenges in these unique contexts. Finally, studies are emerging that quantify the risks from new shipping routes and increasing traffic along the Maritime Silk Road on economic growth 42 , maritime accidents 23 , and carbon emissions 43 , yet the risks to vulnerable habitats and species have yet to be quantified and analyzed in depth. In addition to the features considered in this study, more research is needed investigating how the Maritime Silk Road may impact species’ behaviors, migration patterns, and the spread of invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study 22 , researchers investigated the risks implicit in China’s overseas development finance portfolio to terrestrial biodiversity and Indigenous lands and found these risks to generally be greater than comparable projects financed by the World Bank, particularly in the energy sector. Yet while some studies have discussed the potential implications of increased shipping traffic along the Maritime Silk Road on marine systems 23, 24 or examined the proximity of BRI-affiliated ports to marine ecoregions and threatened species 25 , there remains no comprehensive, quantitative evaluation of the risks to marine socio-ecological systems across China’s diverse portfolio of overseas development finance. This gap is exceptionally concerning given that more than 27 million coastal Indigenous peoples around the world are reliant upon a healthy and functioning marine ecosystem for food and income 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the BN-based approach, the general BN approach has been applied in the maritime domain (Akhtar and Utne 2014;Jiang et al 2020;Wang et al 2017;Wan et al 2019). Furthermore, advanced methods have been introduced to investigate the effectiveness and potential between influential factors such as hybrid ER (Evidential Reasoning)-BN model (Yang et al 2019).…”
Section: Studies Of Methodology: Bayesian Network (Bn)mentioning
confidence: 99%
“…Kum and Sahin (2015) applied a root cause analysis to investigate and reveal the cause of marine accidents/incidents in Arctic waters from 1993 to 2011. The BN was applied to the analysis of collision risk and accident factors in Jiang et al (2020) and . Zhang et al (2021) explored the spatial patterns and characteristics of maritime accidents on a global scale, the characteristics of global maritime accidents are found to be diverse in different regions.…”
Section: Introductionmentioning
confidence: 99%